Roy-Consistent Expectations - Allard, Marie; Bronsard, Camille; Richelle, Yves (Review of Economic Studies, 1990)
In this paper two results are presented. Both refer to the impossibility theorem of Polemarchakis (1983). The Slutsky matrix of intratemporal and intertemporal substitution effects, associated with the individual short-run demand functions, is not arbitrary but symmetric if expectations are (strongly) Roy-consistent (and if the short-run marginal utility of income is continuously differentiable). The same matrix is symmetric and negative semi-definite under strong Royconsistency and a restriction on the expected second-order variation of future real income. These two results suppose a preliminary axiomatization of expectation functions. Weak and strong Roy-consistency are defined within this axiomatization.